Cytogenetic and comorbidity profile of Down syndrome in Mansoura University Children's Hospital, Egypt - El-Gilany, Abdel-Hady (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: Down syndrome (DS) is the most common chromosomal disorder. It has three chromosomal patterns. AIM: To determine the cytogenetic and comorbidity profiles of DS in the Genetic Unit of Mansoura University Children's Hospital, Mansoura, Egypt. MATERIALS AND METHODS: A retrospective analysis was performed on the case records of 712 cytogenetically diagnosed cases of DS at the Genetic Unit of Mansoura University Children's Hospital, Egypt, during a 10-year period. RESULTS: About 19% of the cases had one or more cardiac anomalies and about 8% were hypothyroid. Nondisjunction was the most common type of abnormality, followed by translocation and lastly mosaic: 96.1, 3.1, and 0.8%, respectively. Hypothyroidism was significantly more common in translocation and mosaic karyotypes than in the nondisjunction karyotypes. First and second birth orders were significantly higher in the translocation and mosaic groups than in the nondisjunction group. Mothers are significantly older at the index pregnancy in the nondisjunction group than in the other two groups. We compared our findings with those of previous studies. CONCLUSION: Knowing karyotype of DS will help in genetic counseling of the parents. Wide-scale national community-based survey with DS registry could help in estimating the size of the problem.